Optimization Of Implementation Of System Irrigation For Improving Agricultural Results In Cepu-Blora - Hariyanto Hariyanto; Agustinus Waskito N (International Conference on Coastal and Delta Areas, 2017)
The productivity of agricultural products in Cepu decreases in 2015 -2016 per hectare by an average of 5 tons with the management cost per hectare of 8.6 million rupiah, especially irrigation, which applies electric and diesel pumps during one season, the cost of fuel oil and electric pulse is 4.6 millions of rupiah, the condition is caused by the pattern of irrigation network application has a resistor related to the availability of water and technical management of both wet and dry land has not been optimal, based on the problem the irrigation network model needs optimal assessment, to fulfill the increasing need of irrigation water, one alternative is done the application of an efficient model of irrigation networks with the consideration of knowing the water requirements of both wet and dry crops calculates the existing water discharge as a system of applying the appropriate and efficient pattern of water distribution of irrigation. To fulfill the water needs of the ground and the river water use plants for irrigation is greatly enhanced witches by farmers, by providing the resources (human, equipment, materials) available, optimal modeling of the irrigation system is required. The main objectives of the study to be achieved are 1). Knowing the applied irrigation system, 2). Knowing the crops of agriculture in the last two years. 3). Knowing the availability of water. As a reference to optimization and broader development of irrigation networks in accordance with the availability of water in each farmer's rice fields. The method of the study is quantitative descriptive method that is designed to collect data, by surveying the field to find out the existing irrigation network model, water discharge, crop water requirement, harvested yield. Sampling was conducted by quota sampling all rural of each 3 (three) farmers in 17 (seventeen) villages total sample 51 people who were considered able to represent the farmers. The survey result showed that 17 (seventeen) villages in Cepu there are nine villages which implements irrigation technical and semi technical means such as Ngadon, Jipang, Kapuan, Ngeloram, Nglanjuk, Sumber Pitu, Getas, Kentong and Mernung average debit is 0,020 M3 / second farmer area average 0,50 ha. The results showed that 9 (nine) villages implemented technical irrigation by utilizing underground water as irrigation network in each plot of farmer land there was one village applying an irrigation network of open tapping channel from the river. The results showed that there were 8 (eight) villages with rain-fed irrigation system. Farmers harvested in Cepu from 17 villages on average of 2.35 tons in 2015 and 2.33 in 2016 average land area of 0.5 ha. Types of irrigation networks covered by 0.42 m3 / min average water discharge able to win the average land of 0.5 ha for 40 hours (two days) of water flowing into rice fields, planting pattern with SRI method applying 2/10 to achieve optimal and efficient results water usage Keywords: Irrigation System, Rice Field, Agricultural Product